Jesus the Jew: Nature and Nurture, Ethnicity, and Performance - Levine, Amy-Jill (Studies in Christian-Jewish Relations, 2026)
Jesus’s nature, his ethnic identification, connects him with Jews then and through history; his nurture, the Jewish life in which he was embedded, continues this connection; his lifestyle, his personal and positive decision to live as a Jew as well as his recognition as a Jew by non-Jews commends him to Jews today as part of their history.